Comparative evaluation of different understanding stress factors in medicine teaching women due to the new work routine by COVID-19 (Research, Society and Development, 2021)
The pandemic generated by COVID-19 caused the population to renew and change habits, using preventive methods, such as social isolation, and social distance. It is necessary to take measures such as the adoption of a home office, which directly affected the teachers of the medical course, as they had to adapt the double and triple working hours, with the execution of teaching from their home. Thus, the objective was to evaluate the factors that trigger stress in this new type of work, when compared to the previous day. The research was carried out using the application of questionnaires by online platform with multiple choice questions, containing inclusion and exclusion criteria. Among the interviewees, 55% were stressed, with 40% of them not very satisfied and 35% dissatisfied with the home office modality, this high level of stress according to Cabral (2007) is the main generator of anxiety culminating in the triggering of other behavioral changes. Thus concluding that the application of a questionnaire was effective 2 for this type of analysis, as well as being noticed stressful factors caused by this new modality of work.